Study on nutritional status among children up to five years at tertiary care hospital, HIMS, Sitapur, Uttar Pradesh - Pachori, Ravi; Sillapasuwan, Jiratithigan (International Journal Of Community Medicine And Public Health, 2021)
Background: Undernutrition makes children in particular much more vulnerable to disease and death; around 45% of deaths among children up to 5 years of age are linked to undernutrition and these mostly occur in low and middle-income countries. Malnutrition increases health care costs, reduces productivity, and slows economic growth, which can perpetuate a cycle of poverty and ill-health. Objective of the study was to assess the prevalence of underweight (weight-for-age), sociodemographic profile and to determination of differences exist by gender. Methods: The present study was hospital based descriptive cross-sectional study conducted from June 2019 to December 2019. The sample size calculated was 410, and accounting for 10% nonresponsive, the sample size calculated was 451. The data obtained were compiled and entered in MS-excel 2010 and analysed by using institutional SPSS (22.0). Results: Male children 230 (51.0%) was observed higher proportion as compared to female children 221 (49.0%) and same preponderance difference was found among underweight children. Literate fathers belong to 332 (73.6%) children and illiterate fathers belong to 96 (53.0%) underweight children. literate mother belongs to highly significant 283 (62.8%) children and illiterate mothers belong to highly significant 105 (58.0%) underweight children. Majority of father occupation belongs to other type job 294 (65.2) whereas labour occupation mostly belongs to underweight children 109 (60.2%) highly significant and most of the housewives belong to normal children 361 (80.1%) and underweight children 119 (65.8%) highly significant. Conclusions: Health education on nutrition to parents would be beneficiary for underweight children.